2023
DOI: 10.1158/1538-7445.sabcs22-p4-02-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-02-01: Efficacy of HER2 ADCs against HER2 inhibitor resistance alterations in the PI3K and MAPK pathways in HER2-positive breast cancer

Abstract: Background: HER2 positive (HER2+) breast cancers harboring downstream MAPK or PI3K pathway alterations manifest persistent downstream signaling on anti-HER2 inhibitors with metastatic patients having worse outcomes on first line trastuzumab and pertuzumab (HP) therapy. However, HER2 antibody-drug conjugates (ADCs) are not as dependent upon potent signal transduction inhibition to exert their antitumor effects. To further investigate, we sought to determine whether MAPK and/or PI3K alterations affect the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been shown that T-DM1 keep the biological mechanisms of trastuzumab and that patients who did not have an effect of trastuzumab and taxanes might still respond to T-DM1 [ 14 , 50 , 75 ]. Proposed explanations for differences in response to treatment include downstream signaling alterations, where resistance had been shown for trastuzumab and pertuzumab but not for T-DM1 [ 76 ]. In addition, HER2-positive mouse models have demonstrated that T-DM1 treatment enhances T-cell infiltration compared to trastuzumab, indicating immune-related differences [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that T-DM1 keep the biological mechanisms of trastuzumab and that patients who did not have an effect of trastuzumab and taxanes might still respond to T-DM1 [ 14 , 50 , 75 ]. Proposed explanations for differences in response to treatment include downstream signaling alterations, where resistance had been shown for trastuzumab and pertuzumab but not for T-DM1 [ 76 ]. In addition, HER2-positive mouse models have demonstrated that T-DM1 treatment enhances T-cell infiltration compared to trastuzumab, indicating immune-related differences [ 77 ].…”
Section: Discussionmentioning
confidence: 99%